Ultrastructure of spermatogenesis in the white-lined broad-nosed bat, Platyrrhinus lineatus (Chiroptera: Phyllostomidae) - Beguelini, Mateus R. [UNESP]; Puga, Cintia C. I. [UNESP]; Taboga, Sebastiao R. [UNESP]; Morielle-Versute, Eliana [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
Spermatogenesis, the remarkable process of morphological and biochemical transformation and cell division of diploid stem cells into haploid elongated spermatozoa, is one of the most complex cell differentiations found in animals. This differentiation process has attracted extensive studies, not only because the process involves many radical changes in the cell shape and biochemistry, but also because the phases and steps of differentiation have provided a better basis for analyzing the seminiferous epithelium cycle. Thus, this study aimed to characterize ultrastructurally the spermatogenesis process in the bat Platyrrhinus lineatus in order to provide a basis for determining the stages of spermatogenesis and to facilitate comparisons of the process between bat species and other vertebrates. Based on ultrastructural characteristics three main types of spermatogonia could be accurately identified: A(d), A(p) and B; the differentiation of spermatids was clearly divided into 12 steps (steps 1-3: Golgi phase, steps 4-5: cap phase, steps 6-9: acrosomal phase and steps 10-12: maturation phase). The ultrastructure of spermatozoa, Leydig cells and Sertoli cells was characterized; and some processes including nucleolar disorganization and the formation of synaptonemal complexes, acrosome and chromatoid body were discussed. Based on our results we may conclude that the spermatogenic process of P. lineatus follows the pattern of mammals with some specificity, as the process of formation of the acrosome and the presence of the perfuratorium. By other side, the simpler ultrastructure of its spermatozoon shows a pattern more closely related to the sperm cells of humans and other primates. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Chiroptera; Spermatogenesis; Spermiogenesis; Synaptonemal complex; Ultrastructure